External validation of the SAVED score for venous thromboembolism risk stratification in patients with multiple myeloma receiving immunomodulatory drugs. (5th January 2023) - Dima, Danai; Li, Ang; Granat, Lauren M.; Dhillon, Puneet; Chamseddine, Fatima; Yalamanchali, Anirudh; Mirzai, Saeid; Wei, Wei; Samaras, Christy J.; Valent, Jason; Anwer, Faiz; Khouri, Jack
Summary: Selective patients with multiple myeloma (MM) receiving immunomodulatory drugs (IMiD) are at high risk for venous thromboembolism (VTE). The SAVED score is a VTE risk prediction model recently incorporated into the National Comprehensive Cancer Network (NCCN) guidelines. Using retrospective data from 501 MM patients with new IMiD initiation between 2010 and 2019, we performed the first independent external validation of this model. The cumulative incidence of VTE after IMiD initiation at 6 and 12 months was 32% and 42% in the high‐risk group, versus 6% and 9% in the low‐risk group respectively. The C ‐statistic of the SAVED score to predict VTE within 12 months of IMiD‐based treatment start was 0.74 [95% confidence interval (CI): 0.69–0.78], which outperformed several other VTE risk models in MM patients. Our findings suggest that the SAVED score is an accurate risk assessment tool for VTE stratification in patients initiating IMiD‐containing regimens.